Urban Flooding Vulnerability Analysis Using Weighted Linear Method With Geospatial Information System (African Scientific Reports, 2023)
This study was carried out to investigate the causative factors responsible for flooding in Etsako east, Nigeria. The study applied weighted linear method and geospatial information technology to obtain relevant data which were subjected to analysis. Sentinel 2 imagery of the area was downloaded from the United States Geological Survey (USGS) website and analyzed to produced digital elevation model, rainfall distribution, soil texture classification, topographic wetness index (TWI), hillside slope, land use/cover contour and slope maps of the area. Saaty weighted scale (1 – 5) was used to assign importance to the factors selected. The results presented using relevant maps revealed that, TWI (14%), precipitation (14%), distance to river (12%), elevation (11%) and slope (10%) are the major factors responsible for flooding in the area. Using built up areas only (46.57 km2 ); 38.6% of it is within the risk range of High to very High flood vulnerability, moderate vulnerability zone (17.97 km2 ) occupied 27.28%. Low vulnerability zone occupied 22.05%,(10.27 km2 ) while no vulnerability zone occupied 12.05% (5.61 km2). Communities in the high flood vulnerable region includes Iddo, Iyukwe, Iyogeh, Imiegb and Opepwe; flood control measures and early warning systems should be developed to mitigate the impact of flooding in the area.
Keywords: Flood; Precipitation; Vulnerability; Soil texture; Land use